2021
DOI: 10.1186/s12864-021-07486-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of adaptation to oxygen stress in Nile tilapia (Oreochromis niloticus)

Abstract: Background Tilapia is one of the most abundant species in aquaculture. Hypoxia is known to depress growth rate, but the genetic mechanism by which this occurs is unknown. In this study, two groups consisting of 3140 fish that were raised in either aerated (normoxia) or non-aerated pond (nocturnal hypoxia). During grow out, fish were sampled five times to determine individual body weight (BW) gains. We applied a genome-wide association study to identify SNPs and genes associated with the hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…An i gf1rb polymorphism was reported to be associated with growth traits in the freshwater goby Odontobutis potamophila 100 , and divergence and polymorphism analysis of igf1ra and igf1rb in the orange-spotted grouper ( Epinephelus coioides ) suggested their importance in growth regulation and breeding of this species 101 . Moreover, the involvement of igf1rb in growth during hypoxia was recently reported in a genome-wide association analysis of adaptation to oxygen stress in farmed Nile tilapia ( Oreochromis niloticus ) 102 . Our study revealed a very strong differentiation of the polymorphic HbαD subunit when comparing wild vs farm populations.…”
Section: Discussionmentioning
confidence: 80%
“…An i gf1rb polymorphism was reported to be associated with growth traits in the freshwater goby Odontobutis potamophila 100 , and divergence and polymorphism analysis of igf1ra and igf1rb in the orange-spotted grouper ( Epinephelus coioides ) suggested their importance in growth regulation and breeding of this species 101 . Moreover, the involvement of igf1rb in growth during hypoxia was recently reported in a genome-wide association analysis of adaptation to oxygen stress in farmed Nile tilapia ( Oreochromis niloticus ) 102 . Our study revealed a very strong differentiation of the polymorphic HbαD subunit when comparing wild vs farm populations.…”
Section: Discussionmentioning
confidence: 80%
“…Most of these response processes happen very early at the onset of hypoxia through the activation of pathways depending on already present proteins (Michiels, 2004). Besides that, these adaptive responses to hypoxia depend on a complex regulation that leads to differential expressions of genes and neurotransmitter signaling that changes according to tissue, fish species, and hypoxia condition dependent (Lunde et al, 2011; Solaini et al, 2010; Soto‐Arape et al, 1995; Yu et al, 2021). Studies in the past decades pointed to an essential role of the hypoxia‐inducible factors (HIF) in mammals for gene expression regulation during hypoxia (Majmundar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To further develop the GIFT strain and to enable future improvements, several studies have been investigating the genetic bases underlying traits of economic interest. As a consequence, Quantitative Trait Loci (QTL) associated with sex determination [11], Tilapia Lake Virus resistance [12, 13], feed efficiency [14], adaptation to oxygen stress [15] in the GIFT strain have now been identified.…”
Section: Introductionmentioning
confidence: 99%